Statistical model structure of A1-xZxB2 Laves phase C15 system - the superconducting Ce1-xLaxRu2 alloy - Robouch, B.V.; Marcelli, A.; Saini, N.L.; Kisiel, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Local structure of Ce1-xLaxRu2 system, measured by EXAFS has been re-examined and correlated to the statistical ad hoc model, recently applied to the sphalerite, wurtzite and other intermetallic ternary alloys. The deconvolution of the EXAFS data show that the Ce1-xLaxRu2 ternary system is essentially a mixture of: CeRu2 and LaRu2 binary alloys with a small proportion of the Ce0.5La0.5Ru2 ternary configuration, being maximum for the intermediate concentration. Moreover, the analysis reveals that while the LaRu2 configuration exhibits a Bernoulli random distribution, the presence of a Ce atom affects both the CeRu2 and Ce0.5La0.5Ru2 distributions, strongly favoring the configuration with the CeCe pair, while keeping rare that with a single Ce ion.